M1 macrophage polarization is dependent on TRPC1-mediated calcium entry - Chauhan, Arun (2018)
Fil: Chauhan, Arun. The University of North Dakota. School of Medicine & Health Sciences. Department of Biomedical Sciences and Department of Surgery; United States